Isolation and Characterization of Antigen-Specic Plasmablasts Using a Novel Flow Cytometry–Based Ig Capture Assay - Pinder,CL; kratochvil,S; Cizmeci,D; Muir,L; Guo,Y; Shattock,R; McKay,PF (Journal of Immunology, 2017)
We report the development of a novel flow cytometry–based Ig capture assay (ICA) for the identification and sorting of individual Ab-secreting cells based on their Ag reactivity. The ICA represents a fast and versatile tool for single-cell sorting of peripheral plasmablasts, streamlining subsequent Ab analysis, and cloning. We demonstrate the utility of the assay by isolating Ag-reactive plasmablasts from cryopreserved PBMC obtained from volunteers vaccinated with a recombinant HIV envelope protein. To show the specificity of the ICA, we produced Ag-specific Abs from these cells and subsequently verified their Ag reactivity via ELISA. Furthermore, we used the ICA to track Ag-specific plasmablast responses in HIV-vaccine recipients over a period of 42 d and performed a head-to-head comparison with a conventional B cell ELISpot. Results were highly comparable, highlighting that this assay is a viable alternative for monitoring Ag-specific plasmablast responses at early time points after infection or vaccination. The ICA provides important added benefits in that phenotypic information can be obtained from the identified Ag-specific cells that can then be captured for downstream applications such as B cell sequencing and/or Ab cloning. We envisage the ICA as being a useful tool in Ab repertoire analysis for future clinical trials.